PERLINDUNGAN KONSUMEN AKIBAT KETIDAKSESUAIAN JANJI PELAKU USAHA VOUCHER GAME ONLINE MELALUI MARKETPLACE ITEMKU - Prabanarawata Arfanza (2023)
During the times, the internet began to become something that is often used by people around the world. With regard to the use of the internet in all things, many people are now starting to play online games. This makes people more competitive and buy game vouchers online to support the playing experience and unlock limited features. But with so much interest in online game vouchers, in fact, in online game voucher buying and selling transactions, there are still many discrepancies in the promises made by online game voucher business actors in selling their products, so this is clearly detrimental to consumers. This study raises the formulation of the problem of legal protection for consumers due to discrepancies in buying and selling online game vouchers and what forms of responsibility of business actors and third parties result from these discrepancies. This study aims to analyze consumer protection for their rights that are violated by business actors and analyze the forms of responsibility of business actors and third parties. This research is a type of normative research presented in the form of qualitative analysis, which originates from literature studies and case studies on primary, secondary and tertiary legal materials. The results of the study found that there were still many consumers who were harmed but did nothing because of their ignorance of the protection of their rights so that in this writing the authors explain legal protection for consumers who are harmed so that these consumers are aware that their rights as consumers are protected by law. In addition, business actors who do not comply with their promises regarding the products sold must be fully responsible for all losses suffered by consumers in accordance with those regulated in the UUPK in order to reduce the level of losses for consumers who will purchase online game vouchers on the Itemku marketplace. Keyword : discrepancies, game vouchers, consumer protection